Enhancing Students’ Procedure Text Writing Through Differentiated Learning and the Genre-Based Approach: A Classroom Action Research - Rafsya Rachmani; Yustika Nur Fajriah; Ahmad Farhi Munawir; Hilda Sry Kartika; Muhammad Zanuar Irsyad; Rijal Hengki Adil Al-Awwal (Universitas Subang, 2025)
This study examines the impact of differentiated learning through varied instructional delivery methods on students’ ability to write Procedure Texts. The research was prompted by the need to address students’ diverse learning preferences and interests in the teaching and learning process. While differentiated instruction has been widely recognized as an effective pedagogical approach, limited research has explored its specific influence on students' development in writing skills, particularly in the context of Procedure Texts. To bridge this gap, the study was conducted using a two-cycle Classroom Action Research (CAR) design, incorporating three primary instruments: tests, observations, and interviews. The research participants consisted of thirty twelfth-grade students with four focused participants from a senior high school in Garut. The findings indicate that differentiated learning, which involves tailored instructional strategies for visual learners, read/write learners, auditory learners, and kinesthetics learners, significantly enhances students’ capacity to produce well-structured Procedure Texts. The study specifically highlights improvements in students’ understanding and application of genre moves and language features, demonstrating that customized learning approaches effectively support their writing development. Peculiarly, students could show their improvements in putting the complete generic structure and linguistic features, covering goals, materials/tools, stages, present tense, connectors, adverbials, and imperative sentences. Notably, the achievement rate increased significantly from 56% to 100%, indicating that all students were able to fully apply these elements in their procedural texts. The results underscore the importance of implementing differentiated instruction to cater to students’ individual learning styles, ultimately fostering their academic growth and writing proficiency. This study contributes to the existing body of knowledge on differentiated instruction and offers valuable insights for educators seeking to optimize writing instruction through adaptive teaching strategies.